Asymptomatic Severe Hypocalcemia Secondary to Vitamin D Deficiency in an Elderly Patient - Saleh Aldasouqi; Crystal M. Glassy; Matthew S. Glassy; Anxhela Treska; Molly Caldwell-McMillan; Ved Gossain (Case Reports in Endocrinology)
Objective. To describe an asymptomatic presentation of severe hypocalcemia secondary to vitamin D deficiency in an elderly patient. Methods. We describe the presentation and clinical course of an elderly woman with asymptomatic severe hypocalcemia referred to an endocrinology clinic for hyperparathyroidism. Results. The patient is an 83-year-old Caucasian woman who presented to an endocrinology clinic for evaluation of hyperparathyroidism, with an intact PTH of 462 pg/mL (normal range 14–72 pg/mL). The same lab report included a serum calcium of 5.2 mg/dL (normal range 8–10.5 mg/dL). She displayed no signs or symptoms of hypocalcemia. Given the extreme severity of hypocalcemia and her age, she was hospitalized. Vitamin D deficiency was suspected and was subsequently confirmed with undetectable serum levels. The patient remained asymptomatic throughout her hospital stay. Total and ionized calcium levels at discharge were 7.2 mg/dL and 1.03 mmol/L (normal range 1.1–1.4 mmol/L), respectively. Conclusion. Physicians should exercise prudent management with respect to the vitamin D status of the elderly patient, as certain patients may exhibit severe hypovitaminosis D and hypocalcemia without apparent clinical symptoms.